The Mediating Role of Job Satisfaction in the Effect of Motivation and Career Development on Employee Performance at the Management Unit of Mangusada Regional Hospital, Badung Regency - Ni Made Ayu Sukartini; Ni Luh Putu Agustini Karta; Ni Ketut Dewi Irwanti; I Gede Anindya Perdana Putra (Cita konsultindo, 2026)
Employee performance in public health-care organisations is a key determinant of service quality, yet the factors that shape it continue to yield inconsistent findings. This study analyses the effect of motivation and career development on employee performance and examines the mediating role of job satisfaction at the management unit of Mangusada Regional Hospital, Badung Regency. A quantitative approach was adopted. The population consisted of 125 management employees, and the sample was determined using the Slovin formula with a 5% margin of error, yielding 95 respondents selected through simple random sampling. Data were collected using a five-point Likert-scale questionnaire and analysed with Structural Equation Modelling–Partial Least Squares (SEM-PLS) using SmartPLS software. The results indicate that motivation (β = 0.312; p = 0.048) and career development (β = 0.624; p = 0.000) exert a positive and significant effect on job satisfaction, and that job satisfaction (β = 0.633; p = 0.000) exerts a positive and significant effect on employee performance. However, neither motivation (β = 0.136; p = 0.086) nor career development (β = 0.226; p = 0.062) has a significant direct effect on employee performance. Job satisfaction was found to fully mediate the effects of both motivation (β = 0.398; t = 1.990) and career development (β = 0.395; t = 4.390) on employee performance. The model explains 91.5% of the variance in employee performance.